Efektivitas Sosiodrama untuk Meningkatkan Komunikasi Interpersonal dan Kepercayaan Diri Siswa SMA - Rosita Dyah Primanti; Mudaris Muslim; Ulya Makhmudah (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aims to test the effectiveness of sociodrama techniques in improving students’ interpersonal communication and self-confidence. This research uses the Quasi-Experimental Design method with a Nonequivalent Control Group Design. This study consisted of an experimental group and a control group. Subjects totaling 64 students were selected using the purposive sampling technique, divided into 32 students as the experimental group and 32 students as the control group—data collection techniques using interpersonal communication questionnaires and self-confidence questionnaires. Data analysis used Mann Whitney and Descriptive Analysis Techniques. This study concludes that sociodrama techniques effectively improve students’ interpersonal communication and self-confidence, and sociodrama techniques are more effective in increasing students' independence. self-confidence compared to interpersonal communication of students.Abstrak: Penelitian ini bertujuan untuk menguji keefektifan teknik sosiodrama dalam meningkatkan komunikasi interpersonal dan rasa percaya diri siswa. Penelitian ini menggunakan metode Quasi Exprimental Design dengan Nonequivalent Control Group Design. Penelitian ini ini terdiri dari kelompok eksperimen dan kelompok kontrol. Subjek berjumlah 64 siswa dipilih dengan menggunakan teknik purposive sampling yang terbagi menjadi 32 siswa sebagai kelompok eksperimen dan 32 siswa sebagai kelompok kontrol. Teknik pengumpulan data menggunakan angket komunikasi interpersonal dan angket kepercayaan diri. Analisis data menggunakan uji Mann Whitney dan Teknik Analisis Deskriptif. Kesimpulan dari penelitian ini adalah teknik sosiodrama efektif untuk meningkatkan komunikasi interpersonal dan kepercayaan diri siswa, serta teknik sosiodrama lebih efektif untuk meningkatkan kemandirian siswa. Kepercayaan diri dibandingkan dengan komunikasi interpersonal siswa.